Muscle specific declines in oxygen saturation during acute ambulation with hands-free and conventional mobility devices - Bradley, Adam P.; Roehl, Alexis S.; Smith, Joseph; McGrath, Ryan; Hackney, Kyle J. (Frontiers in Sports and Active Living, 2023)
Disuse is associated with reduced muscle oxygen saturation (SmO2). Improving oxygen delivery to tissues is important for healing, preventing muscle atrophy, and reducing the risk of deep vein thrombosis. Mobility devices are used during disuse periods to ambulate and protect the injured limb. This study examined SmO2 in walking and ambulation with various mobility devices. Thirty-eight participants randomly completed four, ten-minute trials which included: 1) walking, 2) medical kneeling scooter (MKS), 3) hands-free crutch (HFC), and 4) axillary crutch (AC). During each trial, near infrared spectroscopy sensors were placed on the vastus lateralis (VL), biceps femoris (BF), and lateral gastrocnemius (LG) of the right limb. Compared to walking, all mobility devices showed a decline in SmO2 in the VL of 10% (mean ± SD; 75 ± 12% to 65 ± 17%, P < 0.05). In the BF, SmO2 declined 9% in AC compared to walking (76 ± 12% to 67 ± 17%, P = 0.025). In the LG, SmO2 declined in AC (64 ± 16%) compared to MKS (70% ± 15%, P = 0.005). There were no differences in LG SmO2 compared to walking (69 ± 13%) in MKS (P > 0.05) or HFC (65 ± 15%, P > 0.05). In young, healthy volunteers, the use of mobility devices altered muscle oxygenation in several muscles. AC reduced muscle oxygenation in the VL, BF, and LG; while MKS and HFC maintained BF and LG muscle oxygenation at a level consistent with ambulatory walking.